Family-centred care for hospitalised children aged 0-12 years: A systematic review of quasi-experimental studies - Shields, L.; Zhou, Huaqiong; Taylor, M.; Hunter, J.; Munns, Ailsa; Watts, Robin (University of Adelaide, 2012)
Background: Family-centred care is an approach to the planning, delivery, and evaluation of health care that is grounded in mutually beneficial partnerships among health care providers, patients, and families. It is a widely used model in paediatrics, and is felt instinctively to be the best way to provide care to children in hospital. However, its effectiveness has not been established. Objectives: The objective of this review was to identify the effectiveness of family-centred models of care for children (excluding premature neonates) when compared to standard models of care. Inclusion criteria: The review considered quasi-experimental studies of children aged 0-12 years, their families and/or attending health professionals. Interventions for inclusion were family-centred polices, family support, communication, educational and environmental. Outcomes of interest covered three categories: the child, parent and staff. These included psychological, behavioural, physical, developmental, knowledge, satisfaction and attitudinal outcomes. The degree of family-centredness for eligible studies was scored using a modified rating scale based on that developed by Trivette. Types of participants: This review considered studies that included hospitalised children aged 0-12 years (excluding premature neonates), their family and/or health care professionals. Types of intervention(s)/phenomena of interest: The review considered studies that evaluated the effectiveness of family-centred models of care for hospitalised children when compared to standard models of care.Types of studies: The review considered quasi-experimental studies for inclusion to enable the identification of current best evidence regarding the effectiveness of family-centred models of care on child, family and health service outcomes. Quasi-experimental design includes experimental studies in which participants are not randomly assigned to treatment conditions. Types of outcomes: This review considered studies that included the following outcome measures: * Child: psychosocial outcomes, behavioural outcomes, physical health, developmental outcomes, knowledge outcomes, satisfaction, and attitudes;* Parent: psychological health and attitudes; * Staff: psychological health and satisfaction; & * Health services: health-service provision outcomes. Search strategy: The search strategy identified published and unpublished studies dated from 2004 to December 2011. Individual search strategies were developed for six databases and eight resources. Methodological quality: Assessment of the family-centredness - To be considered for inclusion in the review, each study had to meet a pre-established level of family-centredness, as determined using a modified rating scale based on that developed by Trivette. Critical appraisal - The study that met the required degree of family-centredness and other eligibility criteria was then assessed by two independent reviewers for methodological quality prior to inclusion in the review, using standardised critical appraisal instruments from the Joanna Briggs Institute Meta Analysis of Statistics Assessment and Review Instrument. The third reviewer was not required.Data collection: Data were independently extracted from this remaining quasi-experimental study by two independent reviewers, using a standardised data extraction tool. Data were extracted including specific details about the interventions, population, study methods and outcomes of significance to the review question and specific objectives. The third reviewer was not required as there were no disagreements between the reviewers. Data synthesis: Pooling of quantitative data was not possible as only one study was included in this review. Therefore, the quantitative results of the study have been presented in narrative form. Results: Only one study met the inclusion criteria for this review. The study addressed three interventions (information sharing, joint decision making, and participating in care activities), and two outcomes (self-efficacy in participatory involvement in child care and satisfaction with nursing care). The study found that at Day 5 after Paediatric Intensive Care Unit admission the mothers’ self-efficacy in participatory involvement in child care and satisfaction with nursing care in the experimental group were significantly higher than in the control group. Conclusions: Based on this review alone, and the acknowledgement that only one quasi-experimental study met the inclusion criteria, no firm conclusion could be drawn about the effectiveness of family-centred care for children in hospital. However, taken with the recent Cochrane review update on the effectiveness of the model of family-centred care, we suggest that it is time to search for a more effective model of care delivery which supports the child and family without putting undue pressure on families to stay with their child if it is difficult to do so.